Efficacy and Safety of Antifibrinolytic Drugs in Pediatric Surgery: A Systematic Review - Hovgesen, Nadia Thrane; Larsen, Julie Brogaard; Fenger-Eriksen, Christian; Hansen, Anne Kirkeby; Hvas, Anne-Mette (Seminars in Thrombosis and Hemostasis, 2021)
Antifibrinolytic drugs are used to reduce blood loss and subsequent transfusions during surgery and following trauma, but the optimal dosing regimen in the pediatric population is still unresolved. The aim of this systematic review was to evaluate efficacy and safety of antifibrinolytic drugs in pediatric surgery and trauma to determine the optimal dosing regimen. A literature search was performed in PubMed, Embase, Cochrane, and Web of Science on May 3, 2020. We included randomized controlled studies investigating the effect of tranexamic acid (TXA), aprotinin, and epsilon-aminocaproic acid, in terms of reducing blood loss, blood transfusions, reoperations, and rebleeds in pediatric patients aged 0 to 18 years undergoing cardiac surgery, noncardiac surgery, or trauma. Fifty randomized controlled trials (RCTs) were included; 28 RCTs investigated cardiac surgery and 22 investigated noncardiac surgery. No RCTs regarding trauma met the inclusion criteria. All antifibrinolytic drugs reduced postoperative blood loss and transfusions when used in pediatric surgery. The dosing regimen varied between studies, but similar effect sizes were found in terms of reduced blood loss regardless of the cumulative dose used. Few studies found adverse events, and no difference in incidence or type of adverse events was seen between the antifibrinolytic and the placebo group. In conclusion, use of antifibrinolytics is efficient and safe in children undergoing surgery. We propose TXA as the drug of choice based on its level of evidence and safety profile; we recommend a dosing regimen composed of a loading dose of 10 to 15 mg/kg prior to surgery followed by 1 to 5 mg/kg/h as continuous infusion throughout surgery.
Keywords: Antifibrinolytic agents; Tranexamic acid; Aprotinin; Aminocaproic acid; pediatric surgery; blood loss; surgical